Complete sequence of three alpha-tubulin cDNAs in Chinese hamster ovary cells: each encodes a distinct alpha-tubulin isoprotein. - Elliott, E M (1986)
The genome of Chinese hamster ovary (CHO) cells contains a complex family of approximately 16 alpha-tubulin genes, many of which may be pseudogenes. We present here the complete cDNA sequences of three expressed alpha-tubulin genes; one of these genes has been identified only in CHO cells. The noncoding regions of these three CHO alpha-tubulin genes differed significantly, but their coding regions were highly conserved. Nevertheless, we observed differences in the predicted amino acid sequences for the three genes. A comparison of the CHO alpha-tubulin sequences with all of the sequences available for mammals allowed assignment of the alpha-tubulin genes to three classes. The proteins encoded by the members of two of these classes showed no class-specific amino acids among the mammalian species examined. The gene belonging to the third class encoded an isoprotein which was clearly distinct, and members of this class may play a unique role in vivo. Sequencing of the three alpha-tubulin genes was also undertaken in CMR795, a colcemid-resistant clonal CHO cell line which has previously been shown to have structural and functional alterations in its tubulin proteins. We found differences in the tubulin nucleotide sequence compared with the parental line; however, no differences in the alpha-tubulin proteins encoded in the two cell lines were observed.